Correlation of Clinical and Immunological Factors With Overall Survival in Luminal B HER2-Negative Breast Cancer Patients at Prof. Dr. I.G.N.G. Ngoerah Hospital, Denpasar - I Komang Ery Purnama Warsana Putra; IB. Made Suryawisesa; Ketut Sudartana (Epidemiology and Society Health Review (ESHR), 2026)
Background: This study aimed to explore the relationship between clinico-pathological characteristics and overall survival (OS) among patients with Luminal B HER2-negative breast cancer treated at Prof. Dr. I.G.N.G Ngoerah Hospital, Denpasar. Method: A retrospective cohort study was conducted involving 248 patients diagnosed with Luminal B HER2-negative breast cancer between January 2018 and December 2022. Data were collected from medical records and the Bali Cancer Registry, including variables such as age, menopausal status, tumor size (T), nodal involvement (N), metastasis (M), lymphovascular invasion (LVI), tumor-infiltrating lymphocytes (TIL), and treatment modalities. OS was analyzed using the Kaplan–Meier method, and independent prognostic factors were identified through multivariate Cox proportional hazards regression. Results: Most patients were aged ≥40 years (84.8%), premenopausal (58.1%), and had LVI-positive tumors (65.9%). The 5-year OS rate was 60.8%, with a mean survival of 48 months. Kaplan–Meier analysis demonstrated shorter survival among older and postmenopausal patients. In multivariate analysis, TIL (HR = 0.342; 95% CI = 0.171–0.684; p < 0.001), age ≥40 years (HR = 1.459; 95% CI = 1.233–1.875; p < 0.001), and postmenopausal status (HR = 4.553; 95% CI = 2.378–8.733; p < 0.001) were identified as independent predictors of poorer survival. Conclusion: These findings underscore the prognostic importance of immunological and demographic factors in Luminal B HER2-negative breast cancer. The assessment of tumor-infiltrating lymphocytes may serve as a practical and feasible prognostic marker to support risk stratification and individualized management, particularly in resource-limited healthcare settings, while highlighting the need for strengthened early detection and follow-up strategies among older and postmenopausal women.